'S16‐14730C': A high‐yielding conventional soybean cultivar with indeterminate growth habit and multiple disease resistance adapted to the Mid‐South. Issue 2 (21st April 2022) - Chen, P.; Shannon, G.; Scaboo, A.; Crisel, M.; Smothers, S.; Clubb, M.; Selves, S.; Vieira, C. C.; Ali, M. L.; Lee, D.; Lord, N.; Nguyen, H. T.; et al.
Abstract: 'S16‐14730C' (Reg. no. CV‐546, PI 699632) is a conventional maturity group (MG) IV (relative maturity, 4.7) soybean [ Glycine max (L.) Merr.] cultivar released by the University of Missouri–Fisher Delta Research Center breeding program in 2020. It has an indeterminate growth habit, averaging 89 cm in height with a 2.1 lodging score. Plants have purple flowers, tawny pubescence, and tan pod wall color, and seeds have black hilum and 402.8 g kg –1 of protein and 224.0 g kg –1 of oil concentrations. S16‐14730C underwent extensive yield testing and disease evaluation from 2017 to 2020 over a total of 104 environments across 12 states. During the USDA uniform trials in 2018 and 2019, S16‐14730C yielded 4, 192 kg ha –1, equivalent to 99 and 108% of the best checks and overall check mean, respectively. S16‐14730C shows resistance to stem canker and soybean cyst nematode (SCN) HG type 2.5.7 (race 1) and HG type 5.7 (race 3) and moderate resistance to SCN HG type 1.2.5.7 (race 2), southern root‐knot nematode, peanut root‐knot nematode, and charcoal rot. It is susceptible to reniform nematode and phytophthora root rot. S16‐14730C may serve as an excellent choice in regions where a late MG IV conventional line is in demand. Core Ideas: S16‐14730C is a high‐yielding conventional soybean cultivar with a relative maturity group of 4.7. S16‐14730C shows consistently high and stable yield performance across the Mid‐South. S16‐14730C is resistant to stem canker and soybean cyst nematode race 3. S16‐14730C is moderately resistant to SCN races 1 and 2, root‐knot nematode, and charcoal rot.